THE FRAGMENTATION OF ENGLISH CONTRACT LAW – FROM A LAW OF CONTRACT TO A LAW OF CONTRACTS (Multidisciplinary Journal of Science and Technology, 2025)
This article explores how English contract law has shifted from a unified body of principles to a series of specialised regimes that reflect the diversity of modern social and commercial relationships. It begins by outlining the classical model of contract law, grounded in freedom of contract and general rules applicable to all agreements. The discussion then examines Atiyah’s influential critique, which argues that the idea of a “typical contract” has disappeared, giving way to laws shaped by policy, context, and fairness. Through examples drawn from employment, consumer, construction, and domestic contracts, the paper illustrates how fragmentation operates in practice, resulting in tailored protections and obligations for different contracting parties. The article also considers the continuing debate between those who defend a unified “law of contract” and those who recognise multiple “laws of contracts.” It concludes that while fragmentation reduces coherence and predictability, it has made English contract law more responsive and just in addressing inequality and modern complexity. Overall, the law is evolving not through collapse but through transformation—from a single system into a flexible network of contextual rules designed to meet varied social needs.